Facile fabrication of a novel hybrid nanoparticles by self-assembling based on pectin-doxorubicin conjugates for hepatocellular carcinoma therapy. (12th November 2018) - Ye, Peng-Ju; Huang, Can; Yang, Sa; Gao, Pei; Li, Zhi-Ping; Tang, Si-Yue; Xiang, Ya; Liu, Yu-Feng; Chen, Yu-Ping; He, Dong-Xiu; Yu, Cui-Yun
Abstract: Hepatocellular carcinoma (HCC) is one of the greatest public health problems worldwide, and chemotherapy remains the major approach for the HCC treatment. Doxorubicin (DOX) is one of the anthracycline antibiotics but its clinical use is limited due to its severe cardiotoxicity. In this study, novel hybrid nanoparticles by self-assembling based on pectin-doxorubicin conjugates (PDC-NPs) were fabricated for HCC treatment. The stabilized structure of the PDC-NPs was characterized by methylene blue absorption, the size, zeta potential and the morphology, which was investigated by Zetasizer nanoparticle analyzer and transmission electron microscope (TEM), of nanoparticles. The PDC-NPs achieved a sustained and prolonged release ability, which was illustrated with in vitro drug release profiles, anti-cell proliferation study, cellular uptake assay and in vivo pharmacokinetics analysis. Biocompatibility of the PDC-NPs was assessed with bovine serum albumin (BSA) adsorption test, hemolysis activity examination and viability evaluation of human umbilical vein endothelial cells. Importantly, in vivo studies of the PDC-NPs, which were performed in the athymic BALB/c nude mice, demonstrated that the PDC-NPs significantly reduced the lethal side effect of DOX. Additionally, the H&E staining and serum biochemistry study further confirmed the excellent biological security of the PDC-NPs.